Membrane electrode suitable for low-humidity working condition and preparation method

By covering the catalyst surface of the membrane electrode with ionic liquid and mixing it with ionomers, the problem of low mass transfer efficiency of proton transmission and oxygen in low humidity conditions is solved, and the stable operation and performance improvement of fuel cells under low humidity conditions is achieved.

CN119517998AActive Publication Date: 2025-02-25SHANGHAI JIAOTONG UNIV

Patent Information

Application Number
CN202411447166.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-25
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

Under low humidity conditions, the proton transmission channel of the membrane electrode is cut off, resulting in a decrease in the proton transmission efficiency and an increase in the oxygen mass transfer resistance, affecting the stable operation and performance of the fuel cell.

Method used

By dissolving the ionic liquid in ultrapure water, covering it on the catalyst surface, and mixing it with ionomers, a catalyst slurry is prepared, and a cathode catalytic layer is sprayed to form a catalyst structure covered by ionic liquid to ensure the efficiency of proton transport and oxygen mass transfer.

Benefits of technology

It achieves the efficient transmission of protons and local mass transfer of oxygen under low humidity conditions, improves the wide operating capacity of membrane electrodes and the battery performance under large current density, and reduces the cost of membrane electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517998A_ABST
    Figure CN119517998A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a membrane electrode suitable for a low-humidity working condition, which comprises the following steps: (1) dissolving an ionic liquid in ultrapure water, and uniformly dispersing to obtain an ionic liquid aqueous solution; (2) uniformly mixing the ionic liquid aqueous solution obtained in the step (1) with a catalyst, coating the surface of the catalyst with the ionic liquid, and cleaning and drying the coated catalyst to obtain an ionic liquid coated catalyst; (3) uniformly mixing the ionic liquid coated catalyst obtained in the step (2) with an ionomer and a dispersing solvent, preparing catalyst slurry, and spraying to prepare a cathode catalyst layer; and (4) hot-pressing the cathode catalyst layer and the anode catalyst layer obtained in the step (3) to two sides of a proton exchange membrane to prepare the membrane electrode. Compared with the prior art, the membrane electrode disclosed by the invention can ensure high-efficiency transmission of protons in the catalyst layer under a low-humidity working condition, so that wide-working-condition operation is realized; meanwhile, oxygen mass transfer is enhanced, and the battery performance under high current density is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cells, and in particular to a membrane electrode suitable for low humidity working conditions and a preparation method thereof. Background Art

[0002] Proton exchange membrane fuel cells are the main form of hydrogen energy utilization. They can convert the chemical energy stored in hydrogen into electrical energy through electrochemical methods. They have the advantages of high energy conversion rate, no pollution, and fast dynamic response. At present, the main application direction of fuel cells is new energy vehicles, so they need to cope with variable operating conditions, especially low humidity operating conditions.

[0003] However, proton transport within the catalyst layer in the membrane electrode is highly dependent on the proton transport channel constructed by the hydration of the ionomer. Therefore, under low humidity conditions, the hydration degree of the ionomer decreases, which will lead to the truncation of the proton transport channel. At the same time, low water content will cause changes in the distribution of hydrophilic and hydrophobic water domains within the ionomer of the catalyst layer, which is not conducive to oxygen passing through the ionomer film to reach the catalytic active sites, thereby increasing the local oxygen mass transfer resistance.

[0004] Patent ZL201910585539.0 discloses a membrane electrode preparation method that can improve the low-humidity operating performance of proton exchange membrane fuel cells. By adding an appropriate amount of covalent organic framework material to the cathode catalyst layer and the anode catalyst layer, the membrane electrode of the proton exchange membrane fuel cell has a certain self-humidification ability, so that the fuel cell can operate stably under low humidity conditions; at the same time, since the membrane electrode has a certain self-humidification ability, the proton transfer efficiency inside the battery is also significantly improved, and the current density and power density of the battery are also improved to a certain extent. However, this technology uses covalent organic framework materials to give the membrane electrode a certain water retention capacity, thereby helping proton conduction, rather than providing a new proton transmission channel; at the same time, this technology directly adds triazine covalent organic framework materials to the catalyst layer slurry to directly prepare the catalyst layer. During long-term operation, the triazine covalent organic framework material may dissolve in the product water and be taken away from the catalyst layer, resulting in a decrease in the water retention capacity of the membrane electrode and a weakening of the proton transmission performance. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a membrane electrode and a preparation method suitable for low humidity conditions, so as to ensure proton transport and enhance local oxygen mass transfer.

[0006] The object of the present invention can be achieved by the following technical solution: A method for preparing a membrane electrode suitable for low humidity working conditions, comprising the following steps:

[0007] (1) dissolving the ionic liquid in ultrapure water and dispersing it uniformly to obtain an ionic liquid aqueous solution;

[0008] (2) uniformly mixing the ionic liquid aqueous solution obtained in step (1) with the catalyst, coating the catalyst surface with the ionic liquid, and washing and drying the coated catalyst to obtain an ionic liquid-coated catalyst;

[0009] (3) uniformly mixing the ionic liquid-coated catalyst obtained in step (2) with an ionomer and a dispersing solvent to prepare a catalyst slurry, and spraying the slurry to prepare a cathode catalyst layer;

[0010] (4) Hot pressing the cathode catalyst layer and the anode catalyst layer obtained in step (3) onto both sides of the proton exchange membrane to prepare a membrane electrode.

[0011] Furthermore, the ionic liquid is 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([BMIM][NTF2]).

[0012] Furthermore, the mass ratio of the ionic liquid to ultrapure water in step (1) is 1:200-1:1000.

[0013] Furthermore, the mixing method of the ionic liquid and ultrapure water in step (1) is to add the ionic liquid into the ultrapure water; ultrapure water cannot be added into the ionic liquid. (Adding the ionic liquid first and then adding water may cause local aggregation of the ionic liquid, affecting the dissolution rate and dissolution effect).

[0014] The dispersion method is magnetic stirring, and the dispersion time is 1h-5h.

[0015] Furthermore, the mass ratio of the catalyst to the ionic liquid aqueous solution in step (2) is 1:100-1:5000.

[0016] Further, the coating method in step (2) is rotary evaporation, which specifically includes two stages. The first stage has a rotation speed of 60rpm-80rpm, a water bath temperature of 50℃-60℃, and a time of 1h-10h. A rotation speed that is too low will cause uneven temperature distribution in the eggplant-shaped bottle, and a rotation speed that is too high will cause liquid oscillation; a water temperature that is too low will not achieve the heating effect, and the evaporation rate will be slow. A water temperature that is too high will easily cause liquid boiling; a time that is too short cannot ensure liquid evaporation, and a time that is too long will result in low preparation efficiency. The second stage has a rotation speed of 80rpm-100rpm, a water bath temperature of 60℃-80℃, and a time of 1h-10h. A higher rotation speed, temperature, and sufficient time enhance the interaction between the ionic liquid and the catalyst and the surface of the carbon carrier, and ensure the coating effect of the ionic liquid on the catalyst.

[0017] In the above technical solution, the purpose of washing and drying in step (2) is that after rotary evaporation, excess ionic liquid will be physically mixed with the catalyst and will not be coated on the catalyst surface, so this excess ionic liquid needs to be washed away.

[0018] Furthermore, in step (2), the catalyst is one or more of a carbon-supported platinum catalyst, a carbon-supported platinum alloy catalyst, a core-shell catalyst, and a non-precious metal catalyst; the ionomer is a perfluorosulfonic acid ionomer; and the dispersion solvent is one or more of deionized water, isopropanol, and ethanol. The mass ratio of the catalyst, the ionomer, and the dispersion solvent is 1:(1-5):(100-500).

[0019] Furthermore, the mixing method in step (3) is ultrasonic dispersion, and the dispersion time is 10-60 min;

[0020] The spraying method is electrostatic spraying or ultrasonic spraying.

[0021] Furthermore, in step (4), the hot pressing temperature is 120-150°C and the hot pressing time is 1-10 min, the purpose of which is: (1) to ensure that the anode and cathode catalyst layers are attached to both sides of the proton exchange membrane, and (2) to utilize heating to strengthen the direct interaction between the ionomer and the ionic liquid in the catalyst layer, thereby improving the durability of the catalyst layer structure and membrane electrode performance.

[0022] The present invention also provides a membrane electrode suitable for low humidity working conditions, which is prepared by the above method.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. As a salt that is liquid at room temperature, ionic liquid has the advantages of high ion conductivity, high oxygen solubility, low vapor pressure, good thermal stability and chemical stability. In the present invention, suitable ionic liquid is selected to modify the catalyst surface. Ionic liquid can replace water to form a hydrogen bond network inside the ionomer. The ionic liquid is used to help the sulfonic acid group on the side chain of the ionomer to dissociate and form SO3 - As a transfer site for proton transition (because the ionic liquid selected in the present invention is a proton-type ionic liquid that can dissociate into anions and cations), protons can be conducted even in the absence of water to ensure proton transmission; at the same time, the interaction between the ionomer and the ionic liquid can optimize the microstructure inside the ionomer film and enhance the local mass transfer of oxygen.

[0025] The membrane electrode prepared by the present invention can ensure efficient proton transmission in the catalyst layer under low humidity conditions and achieve wide operating conditions; at the same time, it enhances oxygen mass transfer and improves battery performance under high current density. It is worth noting that this study also found that by modifying the catalyst with ionic liquids, the amount of ionomer can be reduced, which can reduce the cost of the membrane electrode to a certain extent.

[0026] 2. The present invention first coats the ionic liquid on the catalyst surface and then prepares the catalytic layer. The structure formed is: the catalyst surface is first coated with an ionic liquid layer and then coated with an ionomer layer; the interaction between the ionic liquid and the catalyst can be made stronger, and the ionic liquid can be prevented from detaching from the catalytic layer during long-term operation. At the same time, the interaction between the ionomer and the ionic liquid can optimize the microstructure inside the ionomer film, especially avoiding the formation of a dense layer of the ionomer on the catalyst surface (the dense layer will seriously hinder the oxygen mass transfer), thereby enhancing the local oxygen mass transfer.

[0027] 3. Under the condition of 100% relative humidity, the peak power of the membrane electrode prepared by the present invention is increased by about 37% compared with the membrane electrode prepared by the conventional process; under the condition of no cathode humidification, the peak power is increased by about 54% compared with the membrane electrode prepared by the conventional process. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a test performance diagram of Example 1 under high humidity conditions;

[0029] Figure 2 This is a test performance diagram of Example 1 under low humidity conditions;

[0030] Figure 3 This is the test performance diagram of Comparative Example 1 under high humidity conditions;

[0031] Figure 4 This is a test performance diagram of Comparative Example 1 under low humidity conditions;

[0032] Figure 5 This is the test performance diagram of Comparative Example 2 under high humidity conditions;

[0033] Figure 6 This is the test performance diagram of Comparative Example 2 under low humidity conditions. DETAILED DESCRIPTION

[0034] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0035] Unless otherwise specified, the various raw materials and equipment used in the present invention are all commonly used commercially available raw materials and equipment in the art.

[0036] Example 1

[0037] This embodiment provides a membrane electrode and a preparation method suitable for low humidity conditions, comprising the following steps:

[0038] 1. Dissolve 0.1 mg of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt in 49.9 mg of ultrapure water and disperse evenly to obtain an ionic liquid aqueous solution. The dispersion method is magnetic stirring and the dispersion time is 3 h.

[0039] 2. The ionic liquid aqueous solution obtained in the previous step was mixed with 0.2 mg of commercial carbon-supported platinum catalyst, and the ionic liquid was coated on the catalyst surface by rotary evaporation. The rotary evaporation was divided into two stages. The first stage had a rotation speed of 70 rpm, a water bath temperature of 60 ° C, and a time of 3 h. The second stage had a rotation speed of 90 rpm, a water bath temperature of 70 ° C, and a time of 3 h.

[0040] 3. Washing and drying the coated catalyst to obtain an ionic liquid-coated catalyst;

[0041] 4. The ionic liquid-coated catalyst is uniformly mixed with perfluorosulfonic acid ionomer and a dispersing solvent in a mass ratio of 1:2:280, wherein the dispersing solvent is a mixture of deionized water and ethanol in a mass ratio of 80:200, and a catalyst slurry is prepared by ultrasonic dispersion for 20 minutes, and then a cathode catalyst layer is prepared by spraying, and the spraying method is electrostatic spraying commonly used in existing membrane electrode preparation;

[0042] 5. The cathode catalyst layer and the conventional commercially available anode catalyst layer were hot pressed onto both sides of the proton exchange membrane to prepare a membrane electrode. The hot pressing temperature was 130°C and the hot pressing time was 5 min.

[0043] The high humidity test conditions of membrane electrode performance are as follows: hydrogen / air are introduced into the anode / cathode respectively, the working temperature is 80℃, the working pressure is 150kPa, and the relative humidity of the anode and cathode is 100%. The test results are as follows Figure 1 As shown, from Figure 1 It can be seen that the battery performance in the low current density area and the high current density area is good, and the peak power reaches 598mW / cm 2 .

[0044] The low humidity test conditions of membrane electrode performance are as follows: hydrogen / air are introduced into the anode / cathode respectively, the working temperature is 80°C, the working pressure is 150kPa, the relative humidity of the anode is 100%, and the relative humidity of the cathode is 0. The test results are as follows Figure 2 As shown, from Figure 2 It can be seen that under the condition of no cathode humidification, the fuel cell performance has no obvious decline, indicating that the ionic liquid can help the effective transmission of protons in the catalyst layer, and the peak power reaches 500mW / cm 2 .

[0045] Comparative Example 1

[0046] This comparative example provides a conventional membrane electrode and a preparation method, comprising the following steps:

[0047] 1. The commercial carbon-supported platinum catalyst, the perfluorosulfonic acid ionomer and the dispersing solvent were mixed uniformly in a mass ratio of 1:2:280 to prepare a catalyst slurry. The mixing method was ultrasonic dispersion for 20 minutes. The catalyst layer was then prepared by spraying. The spraying method was the same electrostatic spraying as in Example 1.

[0048] 2. The catalyst layer was hot pressed onto both sides of the proton exchange membrane to prepare a membrane electrode. The hot pressing temperature was 130°C and the hot pressing time was 5 min.

[0049] The high humidity test conditions of membrane electrode performance are as follows: hydrogen / air are introduced into the anode / cathode respectively, the working temperature is 80℃, the working pressure is 150kPa, and the relative humidity of the anode and cathode is 100%. The test results are as follows Figure 3 As shown, from Figure 3 It can be seen that the peak power is only 437mW / cm 2 , which is lower than the membrane electrode prepared based on ionic liquid modified catalyst prepared in Example 1.

[0050] The low humidity test conditions of membrane electrode performance are as follows: hydrogen / air are introduced into the anode / cathode respectively, the working temperature is 80°C, the working pressure is 150kPa, the relative humidity of the anode is 100%, and the relative humidity of the cathode is 0. The test results are as follows Figure 4 As shown, from Figure 4 It can be seen that the fuel cell performance decreases significantly after the humidity decreases, indicating that the proton transport in the catalyst layer is limited, and the peak power is only 325mW / cm 2 , which is lower than the membrane electrode prepared based on ionic liquid modified catalyst prepared in Example 1.

[0051] Comparative Example 2

[0052] This embodiment provides a membrane electrode and a preparation method suitable for low humidity conditions, comprising the following steps:

[0053] 1. Dissolve 0.1 mg of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt in 49.9 mg of ultrapure water and disperse evenly to obtain an ionic liquid aqueous solution. The dispersion method is magnetic stirring and the dispersion time is 3 h.

[0054] 2. The ionic liquid aqueous solution obtained in the previous step was mixed with 0.2 mg of commercial carbon-supported platinum catalyst, and the ionic liquid was coated on the catalyst surface by rotary evaporation. The rotary evaporation was divided into two stages. The first stage had a rotation speed of 70 rpm, a water bath temperature of 60 ° C, and a time of 3 h. The second stage had a rotation speed of 90 rpm, a water bath temperature of 70 ° C, and a time of 3 h.

[0055] 3. Washing and drying the coated catalyst to obtain an ionic liquid-coated catalyst;

[0056] 4. The ionic liquid-coated catalyst is uniformly mixed with the perfluorosulfonic acid ionomer and the dispersion solvent to prepare a catalyst slurry. The mixing method is ultrasonic dispersion for 20 minutes. Then, the cathode catalyst layer is prepared by spraying. The spraying method is electrostatic spraying.

[0057] 5. The cathode catalyst layer and the conventional anode catalyst layer were hot pressed onto both sides of the proton exchange membrane to prepare a membrane electrode. The hot pressing temperature was 130°C and the hot pressing time was 5 min.

[0058] The high humidity test conditions of membrane electrode performance are as follows: hydrogen / air are introduced into the anode / cathode respectively, the working temperature is 80℃, the working pressure is 150kPa, and the relative humidity of the anode and cathode is 100%. The test results are as follows Figure 5 As shown, from Figure 5 It can be seen that the battery performance in the low current density region decreases significantly, indicating that the selected ionic liquid not only cannot help conduct protons, but also poisons the catalytic active sites, reducing the performance of the fuel cell. The peak power is only 215mW / cm 2 .

[0059] The low humidity test conditions of membrane electrode performance are as follows: hydrogen / air are introduced into the anode / cathode respectively, the working temperature is 80°C, the working pressure is 150kPa, the relative humidity of the anode is 100%, and the relative humidity of the cathode is 0. The test results are as follows Figure 6 As shown, from Figure 6 It can be seen that the battery performance in the low current density region decreases significantly, indicating that the selected ionic liquid not only cannot help conduct protons, but also poisons the catalytic active sites, reducing the performance of the fuel cell. The peak power is only 182mW / cm 2 .

[0060] By comparing the performance test results of Example 1 and Comparative Example 1, it can be seen that the performance of the membrane electrode prepared based on the ionic liquid modified catalyst is better than that of the membrane electrode prepared based on the commercial catalyst under high humidity and low humidity conditions, indicating that the ionic liquid can not only help the water transport in the catalytic layer, but also improve the oxygen reduction activity of the catalyst to a certain extent. The difference between Comparative Example 2 and Example 1 is only the different types of ionic liquids. From the performance test results, it can be seen that the performance of Comparative Example 2 is much lower than that of Example 1 and also lower than that of Comparative Example 2, indicating that inappropriate ionic liquids not only cannot help conduct protons, but also poison the catalytic active sites and reduce the performance of the fuel cell. Therefore, it is necessary to select a suitable ionic liquid.

[0061] Example 2

[0062] The mass ratio of the ionic liquid to the ultrapure water is 1:450, and the rest is the same as in Example 1.

[0063] Example 3

[0064] The mass ratio of the ionic liquid to the ultrapure water is 1:550, and the rest is the same as in Example 1.

[0065] Comparative Example 3

[0066] The mass ratio of the ionic liquid to the ultrapure water is 1:200, and the rest is the same as in Example 1.

[0067] Comparative Example 4

[0068] The mass ratio of the sub-liquid to the ultrapure water is 1:1000, and the rest is the same as in Example 1.

[0069] The same method as in Example 1 was used to test the performance of the membrane electrode of each example and comparative example. The results are shown in the following table:

[0070]

[0071] The mass ratio of ionic liquid to ultrapure water is very important. It will affect the amount of ionic liquid loaded on the catalyst surface after the catalyst is modified, and thus affect the structure of the catalyst layer. Too much ionic liquid will lead to too high solid content in the catalyst layer, restricting the diffusion of oxygen in the gas phase, causing great concentration polarization losses, and reducing the performance of the fuel cell; too little ionic liquid cannot help conduct protons and cannot be used in low humidity conditions. Therefore, it is necessary to select the appropriate ionic liquid content.

Claims

1. A method for preparing a membrane electrode suitable for low humidity conditions, characterized in that: The following steps are involved: (1) dissolving the ionic liquid in ultrapure water and dispersing it uniformly to obtain an ionic liquid aqueous solution; (2) uniformly mixing the ionic liquid aqueous solution obtained in step (1) with the catalyst, coating the catalyst surface with the ionic liquid, and washing and drying the coated catalyst to obtain an ionic liquid-coated catalyst; (3) uniformly mixing the ionic liquid-coated catalyst obtained in step (2) with an ionomer and a dispersing solvent to prepare a catalyst slurry, and spraying the slurry to prepare a cathode catalyst layer; (4) Hot pressing the cathode catalyst layer and the anode catalyst layer obtained in step (3) onto both sides of the proton exchange membrane to prepare a membrane electrode.

2. The method for preparing a membrane electrode suitable for low humidity conditions according to claim 1, characterized in that: The ionic liquid is 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([BMIM][NTF2]).

3. The method for preparing a membrane electrode suitable for low humidity conditions according to claim 1, characterized in that: The mass ratio of the ionic liquid to ultrapure water in step (1) is 1:200-1:1000.

4. The method for preparing a membrane electrode suitable for low humidity conditions according to claim 1, characterized in that: The ionic liquid and ultrapure water in step (1) are mixed by adding the ionic liquid into the ultrapure water; The dispersion method is magnetic stirring, and the dispersion time is 1h-5h.

5. The method for preparing a membrane electrode suitable for low humidity conditions according to claim 1, characterized in that: The mass ratio of the catalyst to the ionic liquid aqueous solution in step (2) is 1:100-1:5000.

6. The method for preparing a membrane electrode suitable for low humidity conditions according to claim 1, characterized in that: The coating method in step (2) is rotary evaporation, which specifically includes two stages. The first stage has a rotation speed of 60rpm-80rpm, a water bath temperature of 50℃-60℃, and a time of 1h-10h; the second stage has a rotation speed of 80rpm-100rpm, a water bath temperature of 60℃-80℃, and a time of 1h-10h.

7. The method for preparing a membrane electrode suitable for low humidity conditions according to claim 1, characterized in that: The catalyst in step (2) is one or more of a carbon-supported platinum catalyst, a carbon-supported platinum alloy catalyst, a core-shell catalyst, and a non-precious metal catalyst; the ionomer is a perfluorosulfonic acid ionomer; and the dispersing solvent is one or more of deionized water, isopropanol, and ethanol.

8. The method for preparing a membrane electrode suitable for low humidity conditions according to claim 1, characterized in that: The mixing method in step (3) is ultrasonic dispersion, and the dispersion time is 10-60 min; The spraying method is electrostatic spraying or ultrasonic spraying.

9. The method for preparing a membrane electrode suitable for low humidity conditions according to claim 1, characterized in that: In step (4), the hot pressing temperature is 120-150° C. and the hot pressing time is 1-10 min.

10. A membrane electrode suitable for low humidity conditions, characterized in that: The method is prepared by any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing membrane electrode capable of improving low-humidity running performance of proton exchange membrane fuel cell

    CN110380060A

  • Ionic liquid modified oxygen reduction reaction catalyst and preparation method thereof

    CN111957344A

  • Foreground-background two-section type combined catalyst and application thereof

    CN112473744A

  • Preparation method, product and application of oxygen reduction catalyst

    CN117225469A

  • Preparation method of membrane electrode adaptive to low-humidity and low-backpressure working conditions

    CN118472285A

Cited By

  • Catalyst slurry and uniformity control method and application thereof

    CN121769128A